Pengaruh Belanja Pemerintah dan Investasi Daerah terhadap Pertumbuhan Produk Domestik Regional Bruto Provinsi Bengkulu - Della Agustin; Pakri Fahmi; Fitriani Ariska (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This study aims to analyze the effect of regional government expenditure and regional investment on the growth of the Constant Price Gross Regional Domestic Product (GRDP) of Bengkulu Province during the 2010–2024 period. The main problem underpinning this research is the suboptimal utilization of government expenditure in driving productive sectors and the relatively low investment attractiveness in Bengkulu Province. This study employs a quantitative method with a causal associative approach. The research population covers all data on regional government expenditure, regional investment, and constant-price GRDP of Bengkulu Province. The sample was determined through purposive sampling, yielding 14 observations for the 2010–2024 period (excluding 2020 due to Covid-19 pandemic distortions). Secondary data were obtained from BPS, BPKAD, and DPMPTSP of Bengkulu Province. The independent variables are regional government expenditure (X₁) and regional investment (X₂), while the dependent variable is constant-price GRDP (Y). Multiple linear regression using EViews was employed, supplemented by classical assumption tests. The results show that government expenditure has a positive and significant effect on GRDP (prob. 0.0016; coefficient 4.181339), regional investment has a positive and significant effect (prob. 0.0007; coefficient 1.242175), and simultaneously both variables significantly affect GRDP (Prob. F-statistic = 0.000000). The R² value of 0.944851 indicates that 94.48% of GRDP variation is explained by these two variables. Improving government expenditure effectiveness and strengthening the investment climate are key strategies for promoting sustainable economic growth in Bengkulu Province.